2022
DOI: 10.1111/1756-185x.14405
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of coronavirus disease 19 patients with a history of rheumatoid arthritis: A retrospective registry‐based study in Iran

Abstract: Background:We aimed to study the outcomes of coronavirus disease 2019 in patients with a history of rheumatoid arthritis (RA) in Iran, where most patients receive corticosteroids and are at high risk for COVID-19 infection. Method:We collected the demographic, diagnostic, and treatment data of all COVID-19 patients by the clinical COVID-19 registry system. We recruited 38 RA patients and 2216 non-RA patients from the COVID-19 registry. The primary outcome was mortality due to COVID-19. We also studied the ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
11
1
Order By: Relevance
“…Other studies reported worse outcomes in patients with RA with SARS‐CoV‐2 infection (2–7). An observational study during the early stages of the pandemic (OpenSAFELY) reported that people with RA, systemic lupus erythematosus, or psoriasis were more likely to die from COVID‐19 compared with controls after adjusting for age, sex, and comorbidities (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies reported worse outcomes in patients with RA with SARS‐CoV‐2 infection (2–7). An observational study during the early stages of the pandemic (OpenSAFELY) reported that people with RA, systemic lupus erythematosus, or psoriasis were more likely to die from COVID‐19 compared with controls after adjusting for age, sex, and comorbidities (6).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with RA are at higher risk of infections either because of immunomodulatory effects of RA or immunosuppressive agents used to treat RA (1). A few studies have reported that patients with RA are at a higher risk of SARS‐CoV‐2 infection and severe COVID‐19 outcomes (2–7), whereas other studies found that RA does not pose increased risk of worse outcomes (8–11). Factors that could contribute to discordant findings include differences in patient profiles (age/race/ethnicity), analysis methods, comparison groups, COVID‐19 disease severity, RA disease severity, COVID‐19 treatment, and COVID‐19 vaccination status, among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coronavirus disease 2019 (COVID‐19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) virus, is a potentially fatal disease that can spread among different species 1 . It is usually characterized by fever, expectoration, fatigue, anorexia and dyspnea 2–6 . Based on the data reported by the World Health Organization, SARS‐CoV‐2 was estimated to have infected 662 445 150 people and led to 6 704 827 deaths (https://covid19.who.int/) by January 16, 2023.…”
Section: Introductionmentioning
confidence: 99%
“…1 It is usually characterized by fever, expectoration, fatigue, anorexia and dyspnea. [2][3][4][5][6] Based on the data reported by the World Health Organization, SARS-CoV-2 was estimated to have infected 662 445 150 people and led to 6 704 827 deaths (https://covid 19.who.int/) by January 16, 2023. This exponential increase in infections has caused not only tremendous losses to individuals but also significantly affected the global economy.…”
Section: Introductionmentioning
confidence: 99%